Penggunaan Media Geoboard untuk Meningkatkan Hasil Belajar Siswa pada Pembelajaran Matematika Madrasah Ibtidaiyah - Najmudin, Afnan Mochammad; Herlina, N Hani; Fuadi, Diki Najib (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2019)
The preliminary study through preliminary observations found the fact that the learning outcomes of students in the mathematics subjects in grade 3 of SD Plus Al-Mu'aawanah were still low. This is because there are still many students who experience difficulties in working on math problems. Thus, it seems that one of them is needed for geoboard media to improve student learning outcomes on the subject of the concept of flat building. The purpose of this class action research implementation is to improve student learning outcomes in mathematics subjects the subject of the concept of flat building using geoboard media. This research method uses Classroom Action Research (CAR) in the subject of Grade 3 SD Plus Al-Mu'aawanah, amounting to 35 students. This study consisted of 3 cycles, data collection techniques with observation, tests and interviews. Data analysis uses analysis techniques of individual completeness and classical completeness. After conducting research in grade 3 of SD Plus Al-Mu'aawanah, the results showed that: 1) The teacher experienced an increase in the ability to develop RPP using geoboard media with an average value in the first cycle 87.75, cycle II 90.05, and cycle III 92.45. 2) The performance of teachers in the process of implementing learning using media geoboard has increased with an average value in the first cycle 89.72, cycle II 91.47, and cycle III 92.26. 3) Student learning outcomes using geoboard media have increased, with an average value in the first cycle 66.42, cycle II 72.28 and cycle III 81.42. Thus, if the preparation of the RPP and the implementation of learning using geoboard media optimally it will improve student learning outcomes.